Withholding Pantoprazole for Stress Ulcer Prophylaxis in Critically Ill Patients: A Pilot Randomized Clinical Trial and Meta-Analysis*. Issue 7 (July 2017) - Alhazzani, Waleed; Guyatt, Gordon; Alshahrani, Mohammed; Deane, Adam M.; Marshall, John C.; Hall, Richard; Muscedere, John; English, Shane W.; Lauzier, François; Thabane, Lehana; Arabi, Yaseen M.; Karachi, Tim; et al.
Abstract : Introduction: A decreased frequency of upper gastrointestinal bleeding and a possible association of proton pump inhibitor use with Clostridium difficile and ventilator-associated pneumonia have raised concerns recently. The Reevaluating the Inhibition of Stress Erosions Pilot Trial determined the feasibility of undertaking a larger trial investigating the efficacy and safety of withholding proton pump inhibitors in critically ill patients. Methods: In 10 ICUs, we randomized adult ICU patients anticipated to be mechanically ventilated for greater than or equal to 48 hours to receive 40 mg of IV pantoprazole daily or placebo. We excluded patients who had acute or recent gastrointestinal bleed, used dual antiplatelet agents, had a medical condition requiring proton pump inhibitor treatment, or had already received more than one dose of acid suppression daily. Patients, families, clinicians, and research staff were blinded. We conducted a systematic review and meta-analysis of similar trials. Main Results: Ninety-one patients (49 pantoprazole and 42 placebo) from 10 centers in Canada, Saudi Arabia, and Australia were enrolled. All feasibility goals were met: 1) recruitment rate was 2.6 patients per month; 2) consent rate was 77.8%; and 3) protocol adherence was 97.7%. Upper gastrointestinal bleeding developed in 6.1% of patients in the pantoprazole group and 4.8% in the placebo group ( p = 1.0). Ventilator-associated pneumonia developed in 20.4% of patients in the pantoprazole group and 14.3% in the placebo group ( p = 0.58). C. difficile was identified in 4.1% pantoprazole patients and in 2.4% placebo patients ( p = 1.0). We meta-analyzed five trials (604 patients) of proton pump inhibitors versus placebo; there was no statistically significant difference in the risk of upper gastrointestinal bleeding, infections, or mortality. Conclusions: Our results support the feasibility of a larger trial to evaluate the safety of withholding stress ulcer prophylaxis. Although the results are imprecise, there was no alarming increase in the risk of upper gastrointestinal bleeding; the effect of proton pump inhibitors on ventilator-associated pneumonia and C. difficile remain unclear. Abstract : Supplemental Digital Content is available in the text.